Pengenalan Aplikasi Simulator Bank Berbasis Internet Pada Mahasiswa Penyandang Disabilitas - Niken Probondani Astuti Trisutomo; Rizal Bakri (Pengelola Jurnal Politeknik Negeri Ketapang, 2022)
Education is an effort made to be able to develop self-potential, or increase intelligence, both through formal and non-formal education, including persons with disabilities. Barriers experienced by persons with disabilities cause them to require special education services. The bank simulator application is an innovative learning alternative designed to make it easier for lecturers and students with special needs to communicate with each other so that learning objectives can be achieved. The purpose of this service is to provide knowledge to students with special needs about the existence of a bank simulator application as an alternative learning in order to obtain the same learning outcomes as other students in banking practice courses, to provide knowledge to students with special needs about the features contained in the bank simulator application. can be used independently to build knowledge independently so that they can develop creativity and innovation in banking practice courses, and improve the quality of student competence for universities that are ready to use in the banking industry. This service activity was carried out by the Service Team in collaboration with the Department of Extraordinary Education, Faculty of Education, Makassar State University offline on December 16, 2021, which was attended by students with disabilities, deaf external organizations and lecturers. The introduction of the bank simulator application to the community was carried out using the lecture and discussion method.